Adaptation strategies for agricultural water management under climate change in Europe - Luis Garrote, L. (2020)
Here we characterise the main risks across European regions and evaluate adaptation strategies by reviewing over 168 highly relevant publications that appeared in the last 15 years. Based on this extensive database we characterise the effort and benefit of a number of agronomic and policy measures, aiming to develop concrete adaptation plans and responding to concrete regional challenges. The adaptation choices consider current technological perspectives and do not project future technological change; we are certain that technological change will shape some choices for adaptation in the coming decades. The greatest scope for action is in improving adaptive capacity and responding to changes in water demands, however the implementation requires revamping current water policy, adequate training to farmers and viable financial instruments. These results aim to assist stakeholders as they take up the adaptation challenge and develop measures to reduce the vulnerability of the sector to climate change.